2022
DOI: 10.3390/nu14214655
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intermittent Fasting in the Management of Nonalcoholic Fatty Liver Disease: A Narrative Review

Abstract: Intermittent fasting is a non-pharmacological dietary approach to management of obesity and metabolic syndrome, involving periodic intervals of complete or near-complete abstinence from food and energy-containing fluids. This dietary strategy has recently gained significant popularity in mainstream culture and has been shown to induce weight loss in humans, reduce gut and systemic inflammation, and improve gut microbial diversity and dysbiosis (largely in animal models). It has been hypothesized that intermitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 93 publications
(132 reference statements)
0
15
0
Order By: Relevance
“…Methylamine occurs endogenously from amine catabolism. Lavallee et al found that dysbiosis of the gut microbiota in obese patients could promote the conversion of choline to methylamine [ 48 ]. Our previous study revealed that fiber supplementation could improve gut microbiota conditions in obese mice [ 6 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylamine occurs endogenously from amine catabolism. Lavallee et al found that dysbiosis of the gut microbiota in obese patients could promote the conversion of choline to methylamine [ 48 ]. Our previous study revealed that fiber supplementation could improve gut microbiota conditions in obese mice [ 6 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same mechanism characterizes the impact of the use of acute physiological stress strategies, such as intermittent fasting, therapeutic cold, therapeutic heat, and intermittent hypoxia. We speculate that the absence of hormetic triggers in modern life will decrease the transcription of NRF1 and NRF2, subsequently TFAM and mitochondrial transcription factor B2 (TFB2M), and ultimately leading to a decrease in mitochondrial mass ( Kokura et al, 2007 ; Harvie and Howell, 2016 ; Chung et al, 2017 ; Alavi et al, 2021 ; Parsamanesh et al, 2021 ; Zeraattalab-Motlagh et al, 2021 ; Lavallee et al, 2022 ; Pak et al, 2022 ). The absence of hormetic triggers can also alter the activity of PGC-1α, which could result in metabolic dysfunction of tissues, leading to the development of various metabolic diseases ( Vandenbeek et al, 2018 ).…”
Section: Part Ii: Mitochondrial Dysfunction and Its Involvement In Di...mentioning
confidence: 99%
“…mood swings), constipation, headache etc.) [90][91]. For some patient categories (such as pregnant or lactating mothers, older individuals, those with advanced chronic diseases, with eating behavior disorders) there is no sufficient safety data to even consider advising this intervention, and it is prudent to refrain from doing so.…”
Section: Potential Risks Associated With Intermittent Fastingmentioning
confidence: 99%